Best Proximity Points for Generalized α-ψ-Proximal Contractive Type Mappings - Mohamed Jleli; Erdal Karapınar; Bessem Samet (Journal of Applied Mathematics)
We introduce a new class of non-self-contractive mappings. For such mappings, we study the existence and uniqueness of best proximity points. Several applications and interesting consequences of our obtained results are derived.